Real-time voltage regulation using fuzzy logic in single-ended primary-inductor converter for electric energy systems - Mezouari, Mohamed; Megrini, Meriem; Gaga, Ahmed (Computers & electrical engineering, 2025)
Reliable output voltage regulation in SEPIC converters is challenging due to input voltage fluctuations and dynamic load changes, which can lead to instability and degraded performance. To address this problem, this paper proposes a fuzzy logic control (FLC) strategy designed to improve transient response and steady-state accuracy without requiring an exact mathematical model. The study begins with the analytical modeling and component sizing of the SEPIC converter to guarantee continuous conduction mode and stable operation. A two-input fuzzy controller, based on voltage error and error rate, is developed and tested in a model-based design environment using MATLAB/Simulink. Simulation results demonstrate that the proposed controller keeps the output voltage deviation below 2% during input disturbances and achieves faster settling compared to classical PID control. For real-time validation, the FLC is implemented on an STM32F446RE 32-bit microcontroller. Experimental results confirm that the FLC significantly reduces overshoot and settling time, enhancing dynamic performance under variable operating conditions. These findings highlight the suitability of the proposed approach for applications such as electric vehicles, robotics, and smart energy systems where robust and precise voltage regulation is required.